Analysing The Quality Of Accrual Accounting Implementation In Indonesia Local Governments - Irwan Taufiq Ritonga (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2018)
The main objective of this study is to assess the quality of accrual accounting implementation in Indonesia local governments. In the context of Indonesia local government, to the author's knowledge, this study is the first in proposing a concept to assess the quality of accrual accounting, which is based on the timeliness of transaction recognition. The quality of accrual accounting is assessed through five types of accrual transactions, which are converting assets to expenses transactions, accruing unpaid expenses transactions, accruing unpaid assets transactions, accruing uncollected revenues transactions, and converting liabilities to revenues transactions. This research is descriptive qualitative research because this research aims to provide facts about quality of accrual accounting implementation in Indonesia local government. The data used in this study is primary data in the form of questionnaires obtained directly from the respondents. The respondents of this study are people who have experience in preparing the local government financial statements. Results of this study are, first, the quality of accrual accounting implementation in Indonesia is low with the quality score of 48.57%. Second, there is no significant difference in the quality of accrual accounting implementation in local government with unqualified opinions and local government with qualifiedÂ opinions. Third, there is no significant difference in the quality of accrual accounting implementation among types of local governments, namely regency local government, municipal local government, and provincial local government.